Argumentos coringas e a influência na autoria de textos dissertativos-argumentativos : análise de redações do site Brasil Escola - Santos, Letícia (2023)
This project proposes to analyze if the manuals that are sold by youtubers on social media and that present ready-made models of argumentation – the wildcard arguments – have impaired the authorship of possible preparatory students present on the Brasil Escola platform. This study is justified by the concern for the use of these wildcard arguments that, from our perspective, can interfere in students' authorship and arguments. The hypothesis of this work is that students use wildcard arguments in essays today because they are influenced by these explanations available on the internet, as they are digital natives and, consequently, master this more autonomous learning. To carry out this project, we take discussions related to argumentation, media influence, and autorship notion, and we refer to authors such as Perelman and Olbrechts-Tyeca (2005), Possenti (2002), Bakhtin (2003), among others, for the analysis. The results indicate that there is a connection between the arguments present in these manuals and the ones effectively used in the argumentative essays analyzed, and that this may undermine the preparatory students’ authorship.